2019
DOI: 10.3892/mmr.2019.10062
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed gene profile and relevant pathways of the traditional Chinese medicine cinobufotalin on MCF‑7 breast cancer cells

Abstract: Cinobufotalin is a chemical compound extracted from the skin of dried bufo toads that may have curative potential for certain malignancies through different mechanisms; however, these mechanisms remain unexplored in breast cancer. The aim of the present study was to investigate the antitumor mechanism of cinobufotalin in breast cancer by using microarray data and in silico analysis. The microarray data set GSE85871, in which cinobufotalin exerted influences on the MCF-7 breast cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Cinobufotalin was previously found to inhibit the activity of Na + /K + -ATP enzyme ( Akimova et al, 2005 ). In addition, cinobufotalin has inhibitory effects on many tumors, including lung, liver, ovarian, breast, and gastric cancers ( Kai et al, 2014 ; Cheng et al, 2015 ; Afroze et al, 2018 ; Li J. et al, 2019 ; Sun et al, 2019 ). More importantly, cinobufotalin also alters the sensitivity of chemotherapeutic drugs ( Li Y. et al, 2019 ; Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cinobufotalin was previously found to inhibit the activity of Na + /K + -ATP enzyme ( Akimova et al, 2005 ). In addition, cinobufotalin has inhibitory effects on many tumors, including lung, liver, ovarian, breast, and gastric cancers ( Kai et al, 2014 ; Cheng et al, 2015 ; Afroze et al, 2018 ; Li J. et al, 2019 ; Sun et al, 2019 ). More importantly, cinobufotalin also alters the sensitivity of chemotherapeutic drugs ( Li Y. et al, 2019 ; Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NRGPS could independently predict the OS for GC patients. We used the GSEA analysis to investigate the gene sets enriched in the two NRGPS groups in order to more thoroughly examine the function of these three marker genes in GC, and the results showed that the gene sets of the high-NRGPS group were mainly enriched in the "Neuroactive ligand-receptor interaction", "Calcium signaling pathway", "Vascular smooth muscle contraction", and "Focal adhesion", which are associated with tumor development (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The hub genes in module 2 were significantly associated with neuroactive ligand–receptor interaction, pathways in cancer, and Ras-proximate-1 or Ras-related protein 1 (Rap1) signaling pathways. The neuroactive ligand–receptor interaction pathway involves many G-protein-coupled receptors and is one of the most common dysregulated pathways of malignancies, including breast cancer [ 57 ]. Rap1 is a small G protein that regulates diverse processes such as cell adhesion, cell–cell junction formation, and cell polarity, which are critical for cellular migration, invasion, and metastasis [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%